Adsorption of arsenic (V) and nickel (II) binary aqueous solution on chitosan-coated bentonite a batch optimization study - Tiodin, Adrian V.; Dalida, Maria Lourdes P. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The search for effective and economical methods to remove metal contaminants from water/wastewater has always been an area of interest in the industry. As such, adsorption poses as an attractive topic because of its high removal efficiency, cost effectiveness and simplicity of operation. This study focuses on the removal of nickel and arsenic in a binary aqueous solution via batch adsorption with the use of chitosan-coated bentonite (CCB) as a biosorbent. Characterization of CCB shows improved surface area and pore volume when compared to pure chitosan. Optimum conditions for batch adsorption were determined using surface response methodology (RSM). Initial Ni (II) concentration (NiCo: 100-500 mg/L), initial As (V) concentration (AsCo: 200-1,000 µg/L), adsorbent mass (m: 0.2-1.0 g) and pH (4-8) were the parameters considered and the experiments were conducted using central composite design (CCD). The resulting optimum condition was NiC0 = 200 mg/L, AsC0 = 400 µg/L, pH = 7.00, and m = 0.40 g with predicted %removals for Ni(II) and As(V) of 60.19% and 80.32%, respectively. Batch experiments were conducted to fully understand the mechanism and kinetics of Ni(II) and As(V) adsorption on CCB in aqueous solution. The Freundlich isotherm better describes the adsorption of As(V) and Ni(II) in a batch system with coefficients of determination (R2) equivalent to 0.7879 and 0.9969, respectively . Kinetic studies followed the pseudo second order reaction model for the As(V) and Ni(II) with R2 values of 0.9340 and 0.9953, respectivel
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Sewage -- Purification -- Heavy metals remova; Bentonite -- Absorption and adsorptio